Collaborative practices and the management of the triptych cost - quality – time - Miloudi Kobiyh,, Oumelbanine El Gueddar, (International Journal of Scientific Research and Management (IJSRM), 2017)
Collaborative practices are designed to create consistency and compliance in both the activity in the performance of the organization. The management of triplet - cost quality time is at the heart of organizational performance, hence the importance of treating the effect of collaborative practices on the management of these three dimensions. Modes of articulation between cost, quality and time depend largely on the business model and therefore collaborative practices emerged within the organization. We therefore propose a conceptual framework that presents the elements of reflection that allows us to understand the development of this approach to knowledge management and its potential role in the management of the triptych cost - quality - time. Similarly we wonder about the complementarity between sustainable development and management triptych in the performance of the company